Clonal integration benefits an invader in heterogeneous environments with reciprocal patchiness of resources, but not its native congener - Zhang, Xiao-Mei; He, Lin-Xuan; Xiao, Xiao; Lei, Jing-Pin; Tang, Min; Lei, Ning-Fei; Yu, Fei-Hai; Chen, Jin-Song (Frontiers in Plant Science, 2022)
Many of the world’s most invasive plants are clonal, and clonal functional traits are suggested to contribute to their invasiveness. Clonal integration is one of the most important clonal functional traits, but it is still unclear whether clonal integration can benefit invasive alien clonal plants more than native ones in heterogeneous environments with reciprocal patchiness of resources and whether invasive plants show a higher capacity of division of labor than native ones in such environments. We grew connected (allowing clonal integration) and disconnected (preventing clonal integration) ramet pairs of an invasive plant Wedelia trilobata and its occurring native congener W. chinensis in the environment consisting of reciprocal patches of light and soil nutrients (i.e., a high-light but low-nutrient patch and a low-light but high-nutrient patch). Clonal integration greatly promoted the growth of the invasive species, but had no significant effect on the native one. Both invasive and native species showed division of labor in terms of morphology, biomass allocation, and/or photosynthetic physiology, but the capacity of labor division did not differ between the invasive and the native species. We conclude that in heterogeneous environments consisting of reciprocal patches of resources, which are common in nature, clonal integration can confer invasive plants a competitive advantage over natives, but this difference is not related to their capacity of labor division. This study highlights the importance of clonal integration for plants in heterogeneous environments and suggests that clonal integration can contribute to the invasion success of alien clonal plants.